Magnetospheric and ionospheric vortices response to positive solar wind dynamic pressure pulse - Zhao, Huayu; Yang, Huigen; Chen, Xinming; Xing, Zanyang; Hu, Zejun; Huang, Dehong; Li, Bin; Zhang, Beichen; Liu, Jianjun (Frontiers in Astronomy and Space Sciences, 2025)
In this study, we present in-situ observations and global MHD simulations of a clockwise-rotating magnetospheric vortex in the dawnside magnetosphere, accompanied by a conjugate clockwise equivalent ionospheric currents (EICs) vortex following a positive solar wind dynamic pressure pulse. When the pressure pulse reached the magnetosphere, the THEMIS spacecraft located in the dawnside region has observed significant plasma velocity perturbations. Minimum variance analysis (MVA) revealed that these perturbations corresponded to a clockwise-rotating flow vortex. Simultaneously, a conjugate clockwise ionospheric current vortex was detected in the EICs system near the THEMIS magnetic footpoint. These coordinated space- and ground-based observations indicate that the magnetospheric clockwise flow vortex induced by the dynamic pressure pulse is coupled to the ionosphere, producing a corresponding clockwise EICs vortex. Furthermore, global MHD simulations reveal the presence of clockwise and counterclockwise vortices in the dawnside and duskside magnetosphere, respectively, supporting the hypothesis that a dawnside dynamic pressure pulse can generate a clockwise magnetospheric plasma flow vortex.